Sodium-glucose co-transporter-2 inhibitors and euglycemic ketoacidosis: Wisdom of hindsight - Singh, Awadhesh Kumar (Indian J Endocrinol Metab, 2015)
Sodium-glucose co-transporter-2 inhibitors (SGLT-2i) are newly approved class of oral anti-diabetic drugs, in the treatment of type 2 diabetes, which reduces blood glucose through glucouresis via the kidney, independent, and irrespective of available pancreatic beta-cells. Studies conducted across their clinical development program found, a modest reduction in glycated hemoglobin ranging from −0.5 to −0.8%, without any significant hypoglycemia. Moreover, head-to-head studies versus active comparators yielded comparable efficacy. Interestingly, weight and blood pressure reduction were additionally observed, which was not only consistent but significantly superior to active comparators, including metformin, sulfonylureas, and dipeptydylpeptide-4 inhibitors. Indeed, these additional properties makes this class a promising oral anti-diabetic drug. Surprisingly, a potentially fatal unwanted side effect of diabetic ketoacidosis has been noted with its widespread use, albeit rarely. Nevertheless, this has created a passé among the clinicians. This review is an attempt to pool those ketosis data emerging with SGLT-2i, and put a perspective on its implicated mechanism.